More knowledge helps implement change: Evaluation of a training program during educational reform. (June 2019) - Zala-Mezö, Enikö; Raeder, Sabine; Strauss, Nina-Cathrin
Highlights: School-specific learning conditions have an influence on the training results. Lack of supporting conditions can prohibit learning. Strong relationship between knowledge and self-efficacy. Gaining knowledge seems to be a useful way to maneuver changing situations. Abstract: In this study, a training program used during a large-scale reform resulting from the implementation of a new school law was evaluated. The evaluation was theoretically founded on the research of training transfer assuming that new knowledge and skills must be transferred to the work context to ensure the effectiveness of the training. An evaluation was conducted after each training course. In total, 3154 course participants and facilitators from 179 courses provided data. The results indicated that the school-specific learning condition contributes to a positive course evaluation and thus results in higher topic-related knowledge. Topic-related knowledge and positive attitudes toward elements of the new law support the course participants' change-related self-efficacy. The study highlighted the relevance of knowledge and attitudes toward the impending changes. The findings suggest that future training programs should consider previous attitudes of participants as well as the school-specific learning conditions within schools.